1977
DOI: 10.1107/s0567740877004580
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure and superstructure of the K phase, Mn77Fe4Si19

Abstract: The K phase, Mn77Fe4Si~9, is monoclinic, a = 13.362 (1), b = 11.645 (1), c = 8.734 (1) × 2 ,~,,/~ = 90-53 (1) °, 110 x 2 atoms per unit cell, space group C2 (C~). Reflections with odd / are quite weak, indicating that the full cell represents a superstructure. The structure model for the substructure was derived from the aspects of the diffraction pattern that resemble the o-FeCr and the 6-MoNi patterns, and with the help of a threedimensional Patterson function. It was refined by full-matrix anisotropic least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The average percentage of Mn on the sites surrounding a particular site increases with the decrease of the Mn content of that site. The same result was previously obtained for the X phase (Mn45Co40Si15; Manor, Shoemaker & Shoemaker, 1972), the v phase (Mnsl.sSila.5; Shoemaker & Shoemaker, 1971) and the K phase (Mn77Fe4Si19; Shoemaker & Shoemaker, 1977).…”
Section: Ordering Of the Atomssupporting
confidence: 72%
See 1 more Smart Citation
“…The average percentage of Mn on the sites surrounding a particular site increases with the decrease of the Mn content of that site. The same result was previously obtained for the X phase (Mn45Co40Si15; Manor, Shoemaker & Shoemaker, 1972), the v phase (Mnsl.sSila.5; Shoemaker & Shoemaker, 1971) and the K phase (Mn77Fe4Si19; Shoemaker & Shoemaker, 1977).…”
Section: Ordering Of the Atomssupporting
confidence: 72%
“…transition-metal alloys. We have previously reported the structures of the v or N phase (Mns~.sSi~8.5; Shoemaker & Shoemaker, 1971) which is ideally t.c.p., the K phase (Mn77Fe4Si19; Shoemaker & Shoemaker, 1977) which also is ideally t.c.p., and the D phase (MnsSi2; Shoemaker & Shoemaker, 1976) which is mainly t.c.p, but has some irregular coordinations. An R phase in the Mn-Si system was discovered by Kuzma & Hladyshevskii (1964) and confirmed by Bardos & Beck (1965).…”
Section: Introductionmentioning
confidence: 99%
“…(g) Shoemaker & Shoemaker (1963). (h) Shoemaker & Shoemaker (1977); data given are for the substructure, which differs from the superstructure only in site compositions. (i) Komura, Sly & Shoemaker (1960); data given are for the hexagonal cell.…”
Section: Discussionmentioning
confidence: 99%
“…Y & K gave examples of how some complex structures can be built up of fragments of the three base structure types, but recognized that 'the most complex structure types are not obliged to be combinations of the corresponding fragments'. That the observation of Y & K has predictive power is illustrated by the fact that the four structure types known to us that have been determined since the (a) (c) publication of the Y & K paper also fit equation (1); these are the K phase Mn77Fe4Si19 (Shoemaker & Shoemaker, 1977), the I phase V41Ni368i23 (Shoemaker & Shoemaker, 1981), the H phase (Ye, Li & Kuo, 1984), and K7Cs 6 (Simon, Br/imer, Hillenkrtter & Kullmann, 1976 This formulation fits all known t.c.p, structure types because…”
Section: Ppqqrxx -~ ( Px2)( Q2r2x3)j( R3x)kmentioning
confidence: 96%
“…Previously we found that these silicon-containing structures are still ideally tetrahedrally close-packed (t.c.p.) up to 19 at.% Si (K phase: Mn77Fe4Si19, Shoemaker & Shoemaker, 1977), whereas in the D phase with 29 at.% Si (MnsSi 2, Shoemaker & Shoemaker, 1976) some irregular coordinations occur. The study of the I phase was of interest because its Si content (up to 27 at.%) lies between that of the K and the D phases.…”
Section: Introductionmentioning
confidence: 99%